Aircraft Touchdown Detection Using Empirical Mode Decomposition - Ozkaya, Hasan; Sakarya, Ufuk (IEEE, 2024)
In this paper, it is aimed to realize aircraft touchdown detection with a low-budget method that does not require high processing capacity. For this reason, the main motivation of the proposed method is to accurately report the aircraft's transition to ground mode when it touches the ground and to provide accurate time information for calculations that can be commented on the hardness of the landing. In this paper, for aircraft touchdown detection, the speed and acceleration data are first filtered using empirical mode decomposition (EMD) and the filtered data is processed using continuous wavelet transform (CWT). According to the experimental results, it has been shown that the proposed method largely eliminates undesirable frequency effects compared to the comparative methods.
Keywords: Aircraft Touchdown Detection; Empirical Mode Decomposition; Computer Science; Engineering; Telecommunications